LamaGOET: an interface for quantum crystallography. Issue 3 (2nd May 2021) - Malaspina, Lorraine A.; Genoni, Alessandro; Grabowsky, Simon
Abstract : The program lamaGOET serves as an interface between quantum‐mechanical and crystallographic refinement software to enhance the flexibility of the quantum‐crystallographic methods Hirshfeld atom refinement and X‐ray constrained wavefunction fitting. Abstract : In quantum crystallography, theoretical calculations and crystallographic refinements are closely intertwined. This means that the employed software must be able to perform both quantum‐mechanical calculations and crystallographic least‐squares refinements. So far, the program Tonto is the only one able to do that. The lamaGOET interface described herein deals with this issue since it interfaces dedicated quantum‐chemical software (the widely used Gaussian package and the specialized ELMOdb program) with the refinement capabilities of Tonto . Three different flavours of quantum‐crystallographic refinements of the dipetide glycyl‐l ‐threonine dihydrate are presented to showcase the capabilities of lamaGOET : Hirshfeld atom refinement (HAR), HAR‐ELMO, namely HAR coupled with extremely localized molecular orbitals, and X‐ray constrained wavefunction fitting.